The Impact of ESG Disclosure on Stock Prices: Evidence from the Manufacturing Industry in Indonesia - apik, rafika; Reny Aziatul Pebriani (Jurnal Akuntansi, 2025)
This study investigates the relationship between Environmental, Social, and Governance (ESG) disclosure and stock price performance among publicly listed companies in [Indonesia/your specific context]. Using panel data regression analysis on firms’ ESG reports and daily stock prices over the period [insert years, e.g., 2020–2023], this research examines whether higher transparency in ESG practices leads to improved investor confidence and, consequently, higher stock valuations.The results indicate that firms with more comprehensive ESG disclosures experience a statistically significant positive effect on stock prices, suggesting that investors reward companies perceived as more sustainable and socially responsible. Moreover, the analysis shows that the environmental and governance dimensions of ESG disclosure have a stronger impact on stock price movements compared to the social dimension.These findings highlight the importance of ESG transparency as a strategic tool for companies seeking to enhance market value and attract long-term investors. This study contributes to the growing literature on sustainable finance by providing empirical evidence from [Indonesia/your specific context] and underscores the need for regulators to strengthen ESG reporting standards.